Pembuatan geopolimer dari metakaolin dan abu terbang - Tjokorde Walmiki Samadhi; Pambudi Pajar Pratama (Jurnal Teknik Kimia Indonesia, 2013)
SYNTHESIS OF GEOPOLYMER FROM METAKAOLIN AND FLY ASH.Geopolymer is an inorganic polymer produced by reacting aluminosilicate solids with a strongly basic activator. Geopolymers can be applied as construction adhesives, replacing ordinary Portland cement. Geopolymerization reaction may occur near room temperatures, implying less energy consumption compared to Portland cement. A variety of inorganic wastes may be selected as the aluminosilicate reactant, which makes geopolymer useful in managing solid wastes. This study builds upon a previous preliminary study, which has proven the technical feasibility of using domestically available raw materials to produce geopolymers. This particular study evaluates the resistance of geopolymers to high temperature, which simulates fire in civil structures. A 24 full factorial design experiment has been undertaken to evaluate the impact of aluminosilicate type (metakaolin and fly ash), base activator type (NaOH and KOH), curing temperature (60 and 80 oC), and heating at 800oC for 2 hours on the compressive strength of the mortar. Combining fly ash, KOH, and higher curing temperature produces the highest compressive strength. Heating at 800 oC reduces the strength of metakaolin geopolymer by inducing crystallization which consumes the geopolymer gel phase, but improves the strength of the fly ash geopolymer mortar by increasing the cohesion of fly ash particles.Keywords: geopolymer, mortar, OPC, compressive strength, heat resistance AbstrakGeopolimer merupakan polimer anorganik yang tersusun oleh rantai-rantai atom Al, Si, dan O, dan dihasilkan melalui reaksi padatan aluminosilikat dengan aktivator basa kuat. Geopolimer dapat digunakan sebagai bahan perekat untuk konstruksi sebagai pengganti semen Portland. Reaksi geopolimerisasi dapat berlangsung di sekitar temperatur kamar, sehingga konsumsi energi produksi geopolimer lebih rendah daripada OPC. Berbagai limbah anorganik dapat digunakan sebagai reaktan aluminosilikat, sehingga geopolimer juga berguna dalam pengelolaan limbah padat. Kajian ini merupakan kelanjutan dari kajian awal yang membuktikan kelayakan teknis pemanfaatan bahan-bahan dalam negeri untuk sintesis geopolimer. Kajian ini mengevaluasi daya tahan geopolimer terhadap temperatur tinggi, yang mencerminkan kejadian kebakaran pada struktur bangunan sipil. Suatu percobaan faktorial 24 dijalankan untuk mengevaluasi pengaruh jenis bahan aluminosilikat (metakaolin dan abu terbang), jenis aktivator basa (NaOH dan KOH), temperatur pematangan mortar geopolimer (60 dan 80 oC), serta pemanasan pada 800 oC selama 2 jam terhadap kuat tekan mortar geopolimer. Kombinasi abu terbang, aktivator KOH, serta temperatur pematangan 80 oC memberikan kuat tekan  tertinggi, yang bahkan lebih tinggi daripada mortar OPC. Pemanasan pada 800 oC merusak struktur jaringan geopolimer metakaolin dengan mendorong kristalisasi yang mengkonsumsi fasa gel geopolimer, sementara justru memperkuat geopolimer abu terbang dengan meningkatkan kohesi antara partikel-partikel abu terbang.Kata kunci: geopolimer, mortar, OPC, kuat tekan, daya tahan panas